Compounding human stressors cause major regeneration debt in over half of eastern US forests. Issue 6 (21st March 2019) - Miller, Kathryn M.; McGill, Brian J.
Abstract: The future of temperate forests in the face of global change and anthropogenic stressors remains uncertain. The regeneration stage, which is a critical bottleneck for many organisms, is a key indicator of forest health, future canopy composition and forest adaptive capacity. In trees, seemingly healthy forests can be at long‐term risk due to insufficient juveniles to replace them (regeneration failure), or compositional differences between juveniles and adults (regeneration mismatch). We propose 'regeneration debt' to collectively describe regeneration failure and mismatch in analogy to extinction debt. To demonstrate this concept, we conducted a macroecological analysis of regeneration debt and anthropogenic stressors in eastern US forests. Using U.S. Forest Service‐Forest Inventory and Analysis data, we quantified regeneration debt in 18 states from Maine to South Carolina, and evaluated the influence of site, anthropogenic stressors and climate drivers in the most affected regions. We identified three distinct regions, with little debt in the north, moderate debt in the south and severe regeneration debt in the central, mid‐Atlantic region. In this region, multiple anthropogenic stressors (invasive plants, deer overabundance and land use) were associated with both low‐regeneration abundance and the prevalence of disease‐prone and/or suboptimal species. Synthesis and applications . Without management intervention, the severe regeneration debt in the mid‐Atlantic region will likely lead to long‐term declines in forest cover, with cascading negative effects on forest‐dependent taxa and ecosystem services. Moreover, the location of the regeneration debt, which is at the northern edge of and involves many of the tree species that are predicted to gain suitable habitat in the Northeastern US, has consequences that extend far beyond its current geographic extent. In fact, this regeneration debt may already be functioning as a barrier to poleward tree migration. Our results demonstrate the value of regeneration debt as an indicator of ecosystem health and forest adaptive capacity. Abstract : Without management intervention, the severe regeneration debt in the mid‐Atlantic region will likely lead to long‐term declines in forest cover, with cascading negative effects on forest‐dependent taxa and ecosystem services. Moreover, the location of the regeneration debt, which is at the northern edge of and involves many of the tree species that are predicted to gain suitable habitat in the Northeastern US, has consequences that extend far beyond its current geographic extent. In fact, this regeneration debt may already be functioning as a barrier to poleward tree migration. Our results demonstrate the value of regeneration debt as an indicator of ecosystem health and forest adaptive capacity.